An industrial quality control study on Kimberly-Clark Philippines Inc. - Castillejo, Kristian John; Magnampo, Ayesa (Quezon City College of Engineering, University of the Philippines Diliman, 2006)
Kimberly-Clark Philippines, Inc. manufactures health and hygiene products for over 40 years. The products are classified into four main segments. Infant Care, Feminine Care, Family Care, and Professional product. Disposable diapers and other related products are under infant Care segment. Moreover, Family Care segment is in-charge on facial and bathroom tissue. Feminine Care segment is responsible for panty-liners, feminine pads, and the like. Lastly, Professional Product segment takes care of other products intended for household use. An industrial quality control study is conducted on the company to address quality related problems. The main focus of the study is on the leg elastic area of Product X. The two major quality characteristics evaluated were leg elastic tension and leg elastic creep. Failure mode, Effects, and Critically Analysis (FMECA) was used to determine the most problematic inspection process throughout the production and it was found out that its work-in process inspection. Statistical Process Control (SPC) was directly employed. First, control charts (both variables and attributes) were used to evaluate the stability of the process. Control chart for individual measurements and moving range chart was used because the samples are homogenous and there's no basis for rational subgrouping. Samples which violated at least one of the eight tests were eliminated after looking for the assignable cause and the new control limits which will be used for future samples were computed. The work schedule of the workers and the shift of the teams were the usual assignable causes After making the process stable (in statistical control) through the use of control charts, process capability analysis followed. It was found out that the potential capability is high while the actual capability is low. The process is off-centered. Moreover, for the leg elastic creep,the defective parts per million produced is high. The causes of these failures were the work schedule of workers, shift of team of workers, and sometimes the machine settings. The group highly recommends the use of SPC in order to monitor the process every now and then. The control limits of the control charts should be reviewed and revised so that the process would be more stable. For the process capability analysis, the company should reduce the width of the specification limits and conduct further study on the performance of production. This would help make the process centered (potential and actual capabilities equal). Moreover, the work schedule of the workers should be reviewed and the machines used for production should be maintained well. These are the primary factors that affect the stability and capability of the process. For the areas for further study, the group suggests flap elastic area, flap leakage, and liner wettability of Product X. Together with these quality characteristics, cost analysis is also important to study further.
Submitted in partial fulfillment of the course requirements in IE 135 : Industrial quality control.
Keywords: Kimberly-Clark Corporation; Diapers; Quality control